Knee isokinetic strength in adults with cerebral palsy and of the persons without disabilities: a integrative literature review (Research, Society and Development, 2022)
Objective: To verify the evidences presented by previus studies that compared isokinetic strenght of the muscles that move the knee of adults with CP with a control group or with reference values of persons without disabilities. Method: Bibliografh researches were carried out in the databases: PubMed, LILACS, Cochrane Central Register of Controlled Trials (CENTRAL), Physiotherapy Evidence Database (PEDro) e SciELO, articles published from the beginning of each database until January 2022 were searched. The search terms used were “cerebral palsy”; "adult"; “isokinetic” or “isokinetic”; “dynamometer” or “dynamometry”; “knee”, in Portuguese and English. Results: A total of 69 articles were found in the initial search (PubMed= 34, LILACS=12, Cochrane CENTRAL= 8, PEDro= 9 and SciELO= 6). After removing the duplicates, 46 studies remained. In the first screening by title and abstract 11 studies were selected. After reading these 11 articles in full and applying the eligibility criteria, a total of 4 articles remained. Final considerations: Studies report that most parameters of physical capacity can be assessed viable and reliable in adults with CP with GMFCS levels I and II, that adults with CP have lower isokinetic and isometric strength of extension than adults without CP, that soccer players with CP and hemiparesis had lower peak torque and mean power on the involved side, had lower peak torque values than predicted values for individuals without physical disabilities and had muscle balance between knee flexors and extensors.